Respostas

A melhor resposta!
2013-08-30T17:25:34-03:00
A) m² - 6m - 9 = 0 
Δ = (-6)² - 4.1.(-9)
Δ = 36 + 36
Δ = 72

m = -(-6) +/- √72 / 2.1
m = 6 +/- 6√2 / 2

m' = 6 + 6√2 / 2
m' = 3 + 3√2

m'' = 6 - 6√2 / 2
m'' = 3 - 3√2

B) z² - z - 12 = 0 
Δ = (-1)² - 4.1.(-12)
Δ = 1 + 48
Δ = 49

z = -(-1) +/- √49 / 2.1
z = 1 +/- 7 / 2

z' = 1 + 7 / 2
z' = 8/2
z' = 4

z'' = 1 - 7 / 2
z'' = -6/2
z'' = -3

c) t² + 5t + 6 = 0
Δ = 5² - 4.1.6
Δ = 25 - 36
Δ = -9

t = -5 +/- √-9 / 2.1
Não há raízes para essa equação, porque não existe raiz de números negativos.
 
D) x² + 2x - 3 = 0 
Δ = 2² - 4.1.(-3)
Δ = 4 + 12
Δ = 16

x = -2 +/- √16 / 2.1
x = -2 +/- 4 / 2

x' = -2 + 4 / 2
x' = 2/2
x' = 1

x'' = -2 - 4 / 2
x'' = -6/2
x'' = -3

E) x² + 3x + 5 = 0 
Δ = 3² - 4.1.5
Δ = 9 - 20
Δ = -11

x = -3 +/- 
√-11 / 2.1
Não há raízes para essa equação, porque não existe raiz de números negativos.

F) 2x² - 7x + 3 = 0
Δ = (-7)² - 4.2.3
Δ = 49 - 24
Δ = 25

x = -(-7) +/- √25 / 2.2
x = 7 +/- 5 / 4

x' = 7 + 5 /4
x' = 12/4
x' = 3

x'' = 7 - 5 / 4
x'' = 2/4 :2
x'' = 1/2 
2 5 2